2003
DOI: 10.1080/01650250143000526
|View full text |Cite
|
Sign up to set email alerts
|

Possible selves and illness: A comparison of individuals with Parkinson's disease, early-stage Alzheimer's disease, and healthy older adults

Abstract: This study examined how future self-representations are affected by two different chronic illnesses, one focused on cognitive losses, early-stage Alzheimer's disease (AD), and one focused on physical losses, Parkinson's disease (PD). The impact of illness on possible selves (perceptions of self in the future) was made salient by a comparison with healthy older adults in order to better understand developmental issues in later life. Findings show that although there were no differences in the total number of do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 36 publications
3
36
0
Order By: Relevance
“…By shifting the point of comparison from symptom severity to exercise and coping abilities, participants developed hope that they, too, would be able to overcome similar challenges when their disease progressed, demonstrating considerable resilience. This reframing reflects a self-regulatory process of refocusing on controllable factors and letting go of uncontrollable factors that can alleviate the diminished perceived GROUP EXERCISE FOR PEOPLE WITH PARKINSON'S 28 control that is often experienced in chronic illness (Frazier, Cotrell, & Hooker, 2003). The reticence to participate due to fear of identifying with those with more advanced stages of the disease is similar to that documented in studies of group exercise for breast cancer survivors (McDonough, Sabiston, & Ullrich-French, 2011), although it appeared to be more pervasive in the present study, perhaps due to the differences in illness trajectory between cancer and PD.…”
Section: Discussionmentioning
confidence: 99%
“…By shifting the point of comparison from symptom severity to exercise and coping abilities, participants developed hope that they, too, would be able to overcome similar challenges when their disease progressed, demonstrating considerable resilience. This reframing reflects a self-regulatory process of refocusing on controllable factors and letting go of uncontrollable factors that can alleviate the diminished perceived GROUP EXERCISE FOR PEOPLE WITH PARKINSON'S 28 control that is often experienced in chronic illness (Frazier, Cotrell, & Hooker, 2003). The reticence to participate due to fear of identifying with those with more advanced stages of the disease is similar to that documented in studies of group exercise for breast cancer survivors (McDonough, Sabiston, & Ullrich-French, 2011), although it appeared to be more pervasive in the present study, perhaps due to the differences in illness trajectory between cancer and PD.…”
Section: Discussionmentioning
confidence: 99%
“…Possible selves capture the dynamic and goal-oriented aspects of personality and have been defined as personalized hoped-for and feared images of the self in the future that direct behavior over time (Cotrell & Hooker, 2005;Markus & Nurius, 1986). Studies on possible selves have shown that the contents of possible selves mirror age-related themes of life and that, in later adulthood, health, cognitive functioning, and social relationships are among the predominant themes (Cross & Markus, 1991;Frazier, Cotrell, & Hooker, 2003;Smith & Freund, 2002). In this study we examine how possible selves in three salient life domains (health, cognition, and social relationships) translate into daily activities in old age.…”
mentioning
confidence: 99%
“…Identifying pleasurable activities, here named ''techniques to increase happiness'', is a drawn from wider cognitive-behavioural therapy interventions, as first identifying and then engaging in such activities can improve mood, view of self and self-efficacy (Ryan and Deci 2001;Moniz-Cook et al 2009). Goal setting and achievement, as in target 2, is relevant here as this is beneficial to psychological wellbeing, improving self-efficacy, and perceived self-worth (Frazier et al 2003) and sharing goal successes can improve perceived self-efficacy (Bandura and Jourden 1991). Self-acceptance exercises have been developed to emphasis that we all have positive and negative characteristics (Dryden 1998).…”
Section: Target 3: Psychological Wellbeingmentioning
confidence: 99%
“…Berg and Upchurch (2007) found that negotiation and positive validation in the dyad (person with dementia and family/friend/carer) are associated to better coping with chronic illness. Family/friends/carers who assume control, aiming to be supportive, may actually be tapping into the person's greatest fears of dependency (Frazier et al 2003). Maintaining involvement in everyday life is important for the dyad (Ablitt et al 2009).…”
Section: Introductionmentioning
confidence: 99%